DOI: 10.33915/etd.6816
|View full text |Cite
|
Sign up to set email alerts
|

Facial Planes as Landmarks for Diagnosis and Treatment Planning

Abstract: Background and Objectives: Diagnosing and treatment planning in contemporary orthodontics is based on comparing elements of craniofacial morphology to selected reference planes. Ideally, a valid reference plane should have good intra-individual reproducibility, low inter-individual variability, and good reliability. The aim of this study was to determine 1.) the reliability and reproducibility of FALL and Glabella Vertical as reference planes 2.) if Glabella Vertical can be used as a frontal reference plane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Glabella Vertical is a line that parallels the head's frontal plane in Natural Head Orientation and passes through the soft tissue glabella point. 6 This study revealed that GALL is located -1mm to 0mm from glabella in 95% of the population. 6 Therefore, it has been proposed that Glabella Vertical can be used in place of FALL, the Forehead's Anterior-Limit Line, which passes through the Forehead's Facial Axis point, FFA.…”
Section: Glabella Verticalmentioning
confidence: 67%
See 3 more Smart Citations
“…Glabella Vertical is a line that parallels the head's frontal plane in Natural Head Orientation and passes through the soft tissue glabella point. 6 This study revealed that GALL is located -1mm to 0mm from glabella in 95% of the population. 6 Therefore, it has been proposed that Glabella Vertical can be used in place of FALL, the Forehead's Anterior-Limit Line, which passes through the Forehead's Facial Axis point, FFA.…”
Section: Glabella Verticalmentioning
confidence: 67%
“…5 A study conducted by Tomblyn found that it is comparable or better to use Glabella Vertical, a vertical line tangent to soft tissue glabella, as a frontal plane compared to FALL. 6 Additionally, there are currently no standard guidelines in which orthodontists and surgeons agree on when determining the optimal AP position of the maxilla when performing orthognathic surgeries. For example, Posnick stated that the optimal AP position of the maxilla is a range of what is considered proportionate and esthetic, not an exact millimeter number.…”
Section: Background and Significancementioning
confidence: 99%
See 2 more Smart Citations
“…They also determined that GALL can be used as a frontal plane for diagnosis and treatment planning. 22 Inclusion of this criteria in diagnosis and treatment planning should be critical to the orthodontist, because patients are exceedingly cognizant of how they look. 23 Attractive facial esthetics is undoubtedly a major treatment goal of orthodontics.…”
Section: Effects Of Upper Incisor Position and Inclination On Smilingmentioning
confidence: 99%